2006
DOI: 10.1038/nature04675
|View full text |Cite
|
Sign up to set email alerts
|

Recursive syntactic pattern learning by songbirds

Abstract: Humans regularly produce new utterances that are understood by other members of the same language community 1 . Linguistic theories account for this ability through the use of syntactic rules (or generative grammars) that describe the acceptable structure of utterances 2 . The recursive, hierarchical embedding of language units (for example, words or phrases within shorter sentences) that is part of the ability to construct new utterances minimally requires a 'context-free' grammar 2, 3 that is more complex th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
443
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 536 publications
(457 citation statements)
references
References 13 publications
11
443
1
2
Order By: Relevance
“…The most important distinction at present appears to be between the levels of regular or Bfinite state^grammars, some types of which are accessible to multiple animal species, and supra-regular grammars that go beyond this (including both context-sensitive and context-free grammars, sometimes termed Bphrase structure grammars^). At present, there are no convincing studies showing the successful acquisition of a supra-regular grammar in a nonhuman animal: for every claimed success (Abe & Watanabe, 2011;Gentner et al, 2006;Rey, Perruchet, & Fagot, 2012), there is a convincing critique (van Heijningen et al, 2009;Beckers et al, 2012;Poletiek et al, 2016). The results of such research have been summarized by Fitch and Friederici (2012), and further explored in important recent work by and Wang, Uhrig, Jarraya, and .…”
Section: Hierarchical Syntaxmentioning
confidence: 99%
“…The most important distinction at present appears to be between the levels of regular or Bfinite state^grammars, some types of which are accessible to multiple animal species, and supra-regular grammars that go beyond this (including both context-sensitive and context-free grammars, sometimes termed Bphrase structure grammars^). At present, there are no convincing studies showing the successful acquisition of a supra-regular grammar in a nonhuman animal: for every claimed success (Abe & Watanabe, 2011;Gentner et al, 2006;Rey, Perruchet, & Fagot, 2012), there is a convincing critique (van Heijningen et al, 2009;Beckers et al, 2012;Poletiek et al, 2016). The results of such research have been summarized by Fitch and Friederici (2012), and further explored in important recent work by and Wang, Uhrig, Jarraya, and .…”
Section: Hierarchical Syntaxmentioning
confidence: 99%
“…They are also able to classify new patterns defined by the grammar while excluding agrammatical patterns. The authors of this study (Gentner, Fenn, Margoliash, & Nusbaum, 2006) concluded that the capacity to classify sequences from recursive, centre-embedded grammars is not uniquely human.…”
Section: The ''Neural Exploitation Hypothesis''mentioning
confidence: 99%
“…Since they did not establish dependencies between words their CFG sentences could be parsed by counting recursion. Likewise, Gentner, Fenn, Margoliash & Nusbaum (Gentner et al, 2006) claimed that their subjects (starlings) learnt CER using the same kind of structures as Fitch and Hauser (Fitch and Hauser, 2004). This in turn elicited some critique: Corballis (Corballis, 2007a;Corballis, 2007b) called attention to the fact that the sentences used could be parsed by simple counting, while others (De Vries et al, 2008;Perruchet and Rey, 2005) showed that in experimental situation similar to that of Fitch & Hauser (Fitch and Hauser, 2004) even human subjects used alternative strategies to solve the tasks.…”
mentioning
confidence: 99%